CryoSat-2 swath interferometric altimetry for mapping ice elevation and elevation change. Issue 6 (15th September 2018) - Gourmelen, N.; Escorihuela, M.J.; Shepherd, A.; Foresta, L.; Muir, A.; Garcia-Mondéjar, A.; Roca, M.; Baker, S.G.; Drinkwater, M.R.
Abstract: For more than 25 years, satellite radar altimetry has provided continuous information on the state of the cryosphere and on its contribution to global sea-level rise. The technique typically delivers maps of ice-sheet elevation and elevation change with 3–10 km spatial resolution and seasonal to monthly temporal resolution. Here we show how the interferometric mode of CryoSat-2 can be used to map broad (5 km-wide) swaths of surface elevation with fine (500 m) spatial resolution from each satellite pass, providing a step-change in the capability of satellite altimetry for glaciology. These swaths of elevation data contain up to two orders of magnitude more surface elevation measurements than standard altimeter products, which provide single elevation measurements based on the range to the Point-Of-Closest-Approach (POCA) in the vicinity of the sub-satellite ground track. The swath elevations allow a more dense, statistically robust time series of elevation change to be formed with temporal resolution of a factor 5 higher than for POCA. The mean differences between airborne altimeter and CryoSat-2 derived ice sheet elevations and elevation rates range from −0.93 ± 1.17 m and 0.29 ± 1.25 m a −1, respectively, at the POCA, to −1.50 ± 1.73 m and 0.04 ± 1.04 m a −1, respectively, across the entire swath. We demonstrate the potential of these data by creating and evaluating elevation models of: (i) the Austfonna Ice Cap (Svalbard), (ii) western Greenland, and (iii) Law Dome (East Antarctica); and maps of ice elevation change of: (iv) the Amundsen Sea sector (West Antarctica), (v) Icelandic ice caps, and (vi) above an active subglacial lake system at Thwaites Glacier (Antarctica), each at 500 m spatial posting – around 10 times finer than possible using traditional approaches based on standard altimetry products.